Liproxstatin-1 improves boar sperm quality during in vitro liquid preservation at 17°C, associated with reduction of oxidative stress and ferroptosis markers - Li, Yang; Liu, Xue; Cheng, Ye; Li, Jingchun; Zhou, Yuling; Guo, Qing (Frontiers in Veterinary Science, 2025)
ObjectiveThe plasma membrane of boar sperm is notably enriched in polyunsaturated fatty acids (PUFAs). During extended liquid storage of boar semen at 17°C, reactive oxygen species (ROS) derived from lipid peroxidation progressively accumulate within sperm cells. Concurrently, the onset of ferroptosis is initiated by the disruption of intracellular redox homeostasis, characterized by an imbalance between the production and elimination of lipid-derived ROS. This study aims to investigate whether the ferroptosis inhibitor Liproxstatin-1 (Lip-1) protects boar sperm quality during 17°C liquid preservation by ameliorating oxidative stress and regulating ferroptosis markers.MethodVarious concentrations of Lip-1 were added to the modified Modena extender, and sperm motility and kinetic parameters were assessed using the CASA system, which facilitated the identification of the optimal Lip-1 concentration. Subsequently, the integrity of the acrosome, plasma membrane, and mitochondrial membrane potential (MMP) of sperm was examined in both the control group and the optimal of Lip-1 group. Additionally, the antioxidant capacity and lipid peroxidation levels of the sperm were evaluated. Furthermore, the ferroptosis inducer Erastin (Era) was utilized to investigate whether Lip-1 could regulate oxidative stress and ferroptosis markers to enhance the liquid preservation efficiency of boar semen at 17°C.ResultVarious concentrations of Lip-1 were added to the modified Modena extender, and the results indicated that, compared to the control group, 0.2 μM of Lip-1 significantly enhanced sperm motility and kinetic parameters. Additionally, a concentration of 0.2 μM Lip-1 significantly enhanced sperm quality, which included improvements in the integrity of the sperm plasma membrane and acrosome, antioxidant capacity, and MMP. Additional, additional tests revealed that Lip-1 can significantly reduce markers of sperm lipid peroxidation during the room temperature preservation of boar semen, including C11-bodipy, MDA, LPO, and improved ferroptosis-related protein GPX4. Furthermore, the ferroptosis inducer Era was utilized, and the results demonstrated that 0.2 μM Lip-1 significantly alleviated the sperm damage induced by Era.ConclusionThe results of this study indicated that Lip-1 significantly enhanced the liquid preservation efficiency of boar semen at 17°C associated with ameliorating oxidative stress and regulating ferroptosis markers, providing both theoretical and practical references for improving the liquid preservation of boar semen.